Analysis of induction phase glucocorticoid use on adrenal suppression in pediatric patients with acute lymphoblastic leukemia - Simbolon, Octaviana; Yulistiani, Yulistiani; Ugrasena, I DG; Qibtiyah, Mariyatul (Folia Medica Indonesiana, 2017)
Glucocorticoids play an important role in the treatment of acute lymphoblastic leukemia (ALL). However, supraphysiological doses may cause suppression of the adrenal. Adrenal suppression resulting in reduced cortisol response may cause an inadequate host defence against infections, which remains a cause of morbidity and mortality in children with ALL. The occurrence of adrenal suppression before and after glucocorticoid therapy for childhood ALL is unclear. The aim of this study is to analysis the effect of glucocorticoid on cortisol levels during induction phase chemotherapy in children with acute lymphoblastic leukemia. A cross-sectional, observational prospective study was conducted to determine the effect of glucocorticoid on cortisol levels in children with acute lymphoblastic leukemia. Patients who met inclusion criteria were given dexamethasone or prednisone therapy for 49 days according to the 2013 Indonesian Chemotherapy ALL Protocol. Cortisol levels were measured on days 0, 14, 28, 42 and 56 of induction phase chemotherapy. There were 24 children, among 31 children recruited, who suffered from acute lymphoblastic leukemia. Before treatment, the means of cortisol levels were 228.95 ng/ml in standard risk group (prednisone) and 199.67 ng/ml in high risk group (dexamethasone). In standard risk group, the adrenal suppression occurs at about day 56. There was a significant decrement of cortisol levels in high risk group in days 14, 28, 42 against days 0 of induction phase (p=0.001). Both groups displayed different peak cortisol levels after 6 week of induction phase (p=0.028). Dexamethasone resulted in lower cortisol levels than prednisone during induction phase chemotherapy in children with acute lymphoblastic leukemia.